Neurobiological Aspects of Mindfulness in Pain Autoregulation: Unexpected Results from a Randomized-Controlled Trial and Possible Implications for Meditation Research - Esch, Tobias; Winkler, Jeremy; Auwärter, Volker; Gnann, Heike; Huber, Roman; Schmidt, Stefan (Frontiers in Human Neuroscience, 2017)
Background: Research has demonstrated that short meditation training may yield higher pain tolerance in acute experimental pain. Our study aimed at examining underlying mechanisms of this alleged effect. In addition, placebo research has shown that higher pain tolerance is mediated via endogenous neuromodulators: experimental inhibition of opioid receptors by naloxone antagonized this effect. We performed a trial to discern possible placebo from meditation-specific effects on pain tolerance and attention. Objectives: It was proposed that (i) meditation training will increase pain tolerance; (ii) naloxone will inhibit this effect; (iii) increased pain tolerance will correlate with improved attention performance and mindfulness. Methods: Randomized-controlled, partly blinded trial with 31 healthy meditation-naïve adults. Pain tolerance was assessed by the tourniquet test, attention performance was measured by Attention Network Test (ANT), self-perceived mindfulness by Freiburg Mindfulness Inventory (FMI). 16 participants received a 5-day meditation training, focusing on body/breath awareness; the control group (N=15) received no intervention. Measures were taken before the intervention and on 3 consecutive days after the training, with all participants receiving either no infusion, naloxone infusion, or saline infusion (blinded). Blood samples were taken in order to determine serum morphine and morphine glucuronide levels by applying liquid chromatography-tandem mass spectrometry analysis. Results: The meditation group produced fewer errors in ANT. Paradoxically, increases in pain tolerance occurred in both groups (accentuated in control), and correlated with reported mindfulness. Naloxone showed a trend to decrease pain tolerance in both groups. Plasma analyses revealed sporadic morphine and/or morphine metabolite findings with no discernable pattern. Discussion: Main objectives could not be verified. Since underlying study goals had not been made explicit to participants, on purpose (framing effects towards a hypothesized mindfulness-pain tolerance correlation were thus avoided, trainees had not been instructed how to ‘use’ mindfulness, regarding pain), the question remains open whether lack of meditation effects on pain tolerance was due to these intended ‘non-placebo’ conditions, cultural effects, or other confounders, or on an unsuitable paradigm. Conclusions: Higher pain tolerance through meditation could not be confirmed.